Numerical design procedure for micro-irrigation manifolds - Merkley, Gary P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
A completely numerical design procedure for micro-irrigation manifolds was developed based on a variation of the hydraulic grade line method. The procedure determines pipe diameters and lengths for telescoping manifolds to minimize pressure variations and improve discharge uniformity. A computer program which implements the procedure is a free download from a web site. The software can accommodate a list of available pipe diameters and other parameters and options to constrain the design results within feasible limits, and it produces a graphical display of the design.
USCID water management conference
Micro-irrigation manifolds
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.